2016
DOI: 10.1111/1759-7714.12350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel saliva‐based epidermal growth factor receptor mutation detection for lung cancer: A pilot study

Abstract: BackgroundThis article describes a pilot study evaluating a novel liquid biopsy system for non‐small cell lung cancer (NSCLC) patients. The electric field‐induced release and measurement (EFIRM) method utilizes an electrochemical biosensor for detecting oncogenic mutations in biofluids.MethodsSaliva and plasma of 17 patients were collected from three cancer centers prior to and after surgical resection. The EFIRM method was then applied to the collected samples to assay for exon 19 deletion and p.L858 mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 31 publications
0
53
0
Order By: Relevance
“…3 Notably, cfDNA and ctDNA can also be detected in urine of patients with bladder cancer, 4-6 colorectal cancer, 7,8 and was recently reported for patients with non-small cell lung cancer (NSCLC). 9,10 Other biological materials, such as stool, 11,12 saliva, 13 cerebrospinal fluid, 14 and pleural fluid 15 can also serve as sources of ctDNA.…”
Section: El L-f Re E CI Rc Ula Ti N G D Na a N D Th E Su B Pop U mentioning
confidence: 99%
“…3 Notably, cfDNA and ctDNA can also be detected in urine of patients with bladder cancer, 4-6 colorectal cancer, 7,8 and was recently reported for patients with non-small cell lung cancer (NSCLC). 9,10 Other biological materials, such as stool, 11,12 saliva, 13 cerebrospinal fluid, 14 and pleural fluid 15 can also serve as sources of ctDNA.…”
Section: El L-f Re E CI Rc Ula Ti N G D Na a N D Th E Su B Pop U mentioning
confidence: 99%
“…Recently, we developed a novel salivary diagnostics platform EFIRM (electric field-induced release and measurement) that can detect and quantify ctDNA with high sensitivity using electrochemical sensor [50]. We tested the ability of EFIRM to detect tyrosine kinase inhibitor-sensitive EGFR mutations (exon 19 deletion and L858R mutations) directly from saliva and plasma of lung cancer patients [50,59]. A receiver-operating characteristic (ROC) curve analysis demonstrated that EFIRM detected EGFR exon 19 deletion and L858R mutation in saliva with an area under the ROC curve (AUC) of 0.94 and 0.96, respectively, suggesting that saliva-based EGFR mutation detection (SABER) met the clinical requirements.…”
Section: Salivaomics In Cancermentioning
confidence: 99%
“…The receiver operating characteristic (ROC) analysis indicated that EFIRM detected the exon 19 deletion with the AUC of 0.94 and the L858R mutation with an AUC of 0.96 [12]. Pu et al used EFIRM to detect exon 19 deletion and L858R mutations in saliva and plasma samples of lung cancer patients [57]. This study resulted in the detection of exon 19 deletion with the AUC of 1.0 in both saliva and plasma samples in lung cancer patients.…”
Section: Saliva Biomarkers Of Cancer Detectionmentioning
confidence: 99%